Bio-fertilizer Impact on Production Efficiency and Yield of Corn (Zea mays) Cultivars Under Water Deficiency - Elnaz Farajzadeh- Memari-Tabrizi; Marzieh Babashpour-Asl (agriTECH, 2021)
The application of bio-fertilizer (Glomus mosseae) and the selection of suitable cultivars are simple solutions to mitigate stress conditions such as water deficiency. This study was conducted in 2016 as a split-plot that was based on randomized complete block design with 3 replications. The effects of irrigation level, bio-fertilizer application and cultivar type on the reproductive efficiency and yield of corn were compared in the field experiment. Irrigation levels (after 70, 110 and 150 mm of pan evaporation) were placed as the main factor in the main plots. Application and non-application of bio-fertilizer (Glomus mosseae) as well as cultivar type (cultivars, 640 and 704) were placed in the subplots to study the physiological differences, reproductive efficiency, and yield of corn. This study showed that the cultivars performed differently in their response to water deficiency. The highest grain yield for 704 cultivars was obtained when we applied irrigation after 70 mm evaporation from pan. When subjected to the treatment of irrigation after 110 and 150 mm evaporation from pan, lower grain yield per unit area of 19% and 50.6%, respectively was recorded. The 640 cultivars produced less yield under full irrigation than 704 cultivars. Water deficiency had no beneficial effects on grain yield per unit area (P > 0.01). It was also observed that bio-fertilizer treatment increased the corn yield by 25.2 %. Water deficiency, bio-fertilizer and cultivar type affected the grain yield as differences were observed in the main components of kernel row number and 100-kernel weight. Water deficiency had no beneficial effects on ‘chlorophyll a’ content, but decreased the content of chlorophyll b. Water deficiency and bio-fertilizer application caused an increase in the catalase and peroxidase content. The best plant performance was observed in plants grown under complete bio-fertilizer (704 cultivar) and at after 70 mm irrigation level. Bio-fertilizers can be used in order to improve corn production and also as environmentally friendly fertilizers under deficit irrigation regimes.